From Hive to Consumer: A Decentralized Blockchain Solution for Real-Time Honey Authenticity Verification and Fraud Prevention - Abeer ALOTAIBI; Amal ALFARSI; Angham ALBELADI; Shahad ALASLANI; Shahad ALFARSI; Rana ALSHAIKH; Arwa MASHAT (Communications of International Proceedings, 2025)
The rise of counterfeit food products, particularly honey, threatens public health and erodes consumer trust, necessitating robust traceability solutions. While blockchain technology has been explored for supply chain transparency, existing systems often lack seamless integration with official regulatory databases, leaving a critical gap in fraud prevention. This study introduces Yaqen, a blockchain-based traceability platform designed to authenticate honey products in Saudi Arabia by generating tamper-proof barcodes for end-to-end supply chain tracking. Unlike conventional systems, Yaqen enhances accountability by directly validating supplier credentials via Wathq, an official government registry, ensuring only verified entities participate. The methodology combines blockchain’s immutability with real-time verification, enabling consumers to scan products and access immutable provenance records. Findings demonstrate that Yaqen effectively mitigates fraud risks by providing a decentralized, transparent ledger while fostering compliance with national regulatory standards. The platform’s success in honey authentication suggests scalability to other high-risk food sectors, offering a model for bridging regulatory oversight with consumer assurance. This study contributes a replicable framework for combating food fraud through technology-driven traceability.
Keywords: blockchain; supply chain traceability; counterfeit prevention; fraudulent goods; Saudi Arabia